EFFICACY ASSESSMENT OF CRYO STORAGE OF DONOR HEARTS BY IMAGEJ BASED IMAGE ANALYSIS - Bao-quan Lin; Sheng-sheng Yang; Zhi-yong Zeng; Cong-wen Zhuang (Российский кардиологический журнал)
Aim. Donor organ injury during cold preservation before transplantation negatively impacts graft survival. The current study was to examine available evidences for the efficacy of different cold storage solutions that are used to preserve donor hearts in vitro prior to orthotopic transplantation.Material and methods. A systematic search of full-length articles published from 1980 to August 2012 was performed in PubMed and Google Scholar. Detailed searches were also made for availability of any sourceware for histopathology images of endomyocardial biopsies of stored hearts.Results. Not even a single controlled trial has been published relating to this topic. However, we assessed all available literature pertaining to this topic, and performed original, simple yet innovative analyses using ImageJ, a Java based image analyses program, to show the tremendous power to objectively examine the efficacy of the storage solution. Our analysis suggest that ImageJ may be conveniently used to obtain evidences (or lack of it) of ischemic injury of donor hearts during cold storage.Conclusions. Even the UNOS database does not provide histopathological evidences of cardiac biopsies of orthotopically transplanted hearts. We, however, make the case of the need for image analyses and making availability of images to allow establishing evidence of the usefulness of these storage solutions. We recommend obtaining endomyocardial biopsy prior to orthotopic transplantation and create a registry of H&E stained slides. This is the only step that will direct us towards evidence based care of such highly critical patients who need the equally challenging surgical intervention of cardiac transplantation.